Diversification of housing sources for military - Chimyshenko S. (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article analyzes current mechanism of serviceman housing support, and highlights new possible ways of improving it through diversification of proper tools and methods in the context of so-called “monetization” of some methods of servicemen social protection.